Transfer of Innovative Technologies in Health Care in Russia and Abroad - Olga PYATAEVA; Elena BORISOVA; Alexey KHARLAMENKOV; Gulmira NURGAZINA; Alexey ALTUKHOV (Communications of International Proceedings, 2021)
The need to distinguish the special characteristics of technology transfer in economic sectors arises in case of technologies or technological components require a certain modification of industries. So intellectual property rights and the physical form in which it is expressed could be fully involved in the production processes. Health care is an economic sector which purpose is to organize and provide accessible health care for the population, and to maintain and improve its standard of health [1]. It is a set of measures of a political, economic, social, legal, scientific, medical, hygienic, epidemiological and cultural nature aimed at preserving and strengthening the physical and mental health of each individual; maintaining his long-term active life and providing him with medical assistance. In this regard, there is some specificity in the implementation of technology transfer processes in the industry, which will be discussed below.
Keywords: Technology Transfer; Health Care; Medicine; Innovative Technologies; Innovation Activity; Transfer of Medical Technology.